Increasing the potential of Cajuput leaf waste as cattle feed through fermentation pretreatment - Ana Widiana; Ukit Ukit; Prayoga Kusumah; Ayu Wiharyati; Hana Hanifah (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2021)
Waste of Cajuput leaves (Melaleuca cajuputi Powell) has the potential to be used as an alternative cattle feed because it has a high nutritional content. The nutritional content of Cajuput leaf waste needs to be improved before being used as an alternative feed. The fermentation process can increase nutrient content in Cajuput leaf waste and increase the organic matter digestibility (OMD), dry matter digestibility (DMD), ammonia (NH3) and volatile fatty acid (VFA). This study aimed to determine the improvement of Cajuput leaf waste nutrition with the help of yeast as well as the effect of fermented Cajuput leaf waste along with a mixture of concentrates and field grass on digestibility, NH3 and VFA which were carried out by in vitro test. The results showed the nutritional content of Cajuput leaf waste fermented by yeast of Aspergillus chevalieri had the best value of protein 16.03%, fiber 16.92% and fat 5.93%. The treatment R4 (50% Cajuput leaf waste + 25% concentrate + 25% field grass) had the best digestibility (DMD= 46.12%; OMD=32.08% ), NH3 (8.37 mM) and VFA (168.5 mM) production.